2023
DOI: 10.3390/buildings13030618
|View full text |Cite
|
Sign up to set email alerts
|

Design of Rural Human Settlement Unit with the Integration of Production-Living-Ecology of China Based on Dynamic Emergy Analysis

Abstract: It is of great theoretical and practical significance to optimize and improve the design of rural human settlement units through system ecology analysis based on emergy evaluation indices. From the perspective of system ecology, the rural living environment system is multivariate and complicated, with strong correlations and obscure boundaries between levels. Therefore, the definition of a rural human settlement unit in China is proposed in this research and can be divided into three scales: the microcosmic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…As difference sources of energy vary in qualities, emergy is used to overcome this barrier. Chang et al [14] employed a dynamic emergy analysis method for the design of a rural human settlement unit integrated with product-living-ecology. They found that the emergy self-sufficiency ratio and sustainable indices decreased over time, from 0.34 to 0.15 and from 0.76 to 0.57, respectively.…”
Section: Energy Savings Through Energy Modeling Prediction and Disagg...mentioning
confidence: 99%
“…As difference sources of energy vary in qualities, emergy is used to overcome this barrier. Chang et al [14] employed a dynamic emergy analysis method for the design of a rural human settlement unit integrated with product-living-ecology. They found that the emergy self-sufficiency ratio and sustainable indices decreased over time, from 0.34 to 0.15 and from 0.76 to 0.57, respectively.…”
Section: Energy Savings Through Energy Modeling Prediction and Disagg...mentioning
confidence: 99%